The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.3109/0284186x.2011.580002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of respiratory motion during IMRT dose delivery

Abstract: For patient specific cases, the model can with good accuracy calculate 3D dose distributions both with and without respiratory motion, and evaluate the dosimetric effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…On the other hand, the minimum dose of moving target was reduced to 6% compared to static even after thirty fractions. Similarly, Mohn and Wasbø[ 41 ] also pointed out that the dose deviation reduction (averaging) with increasing number of fractions is plan and patient specific, and this should be evaluated before the final clinical decision.…”
Section: Mpact Of R Espiration-inducedmentioning
confidence: 99%
“…On the other hand, the minimum dose of moving target was reduced to 6% compared to static even after thirty fractions. Similarly, Mohn and Wasbø[ 41 ] also pointed out that the dose deviation reduction (averaging) with increasing number of fractions is plan and patient specific, and this should be evaluated before the final clinical decision.…”
Section: Mpact Of R Espiration-inducedmentioning
confidence: 99%
“…With a large number of fractions the interplay may average out, as recently reported for a 25 fraction IMRT delivery by Mohn et al [23], however as suggested by the authors this averaging will be patient and plan specific. The amplitude value used in this study (i.e.…”
Section: Discussionmentioning
confidence: 83%
“…19 However, studies have shown that the interplay between organ and MLC motion may average out with a large number of treatment fractions. 20 In addition, the interplay may also be reduced by careful application of motion management techniques such as breath hold.…”
Section: Opening Statementmentioning
confidence: 99%